LAND SUITABILITY EVALUATION FOR BANANA IN JENAWI DISTRICT, KARANGANYAR, INDONESIA - Mujiyo Mujiyo; Fitriana Romdhati; Hery Widiyanto; Aktavia Herawati (Universitas Tadulako, 2021)
The superior banana varieties in Karanganyar Regency, including Jenawi District, have the potential to be developed, but banana development is still constrained by the lack of information regarding land suitability. This study aims to to obtain the land suitability class for banana and its limiting factors, to arrange land management for its development. This research was a descriptive explorative study through a field survey approach, supported by laboratory analysis. Determination of land suitability classes is carried out by matching land characteristics with plant growth requirements. The actual land suitability class for banana plants is not suitable (N) and marginal suitable (S3). The inhibiting factors for banana suitability were low temperature, high rainfall, low P2O5 content, steep slopes, and high erosion hazards. Land improvement effort that can be done include elaborate drainage structure, liming and ameliorant adding, P-fertilizing, planting in line with contour and cover crop planting. Potential land suitability classes for banana are not suitable (N), marginal suitable (S3) and moderately suitable (S2). Jenawi District has sufficient land potential for banana development. Banana development can be carried out on land with moderately suitable potential land suitability by improving the land limiting factors.